Role of Technology in Enabling the Students for Enhanced Learning Outcomes through Self Assessment - Choudhary, Shashikala (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Information and communication technology focus on a progressive path for students to support learning. ICT is an electronic means of information processing, preserving, communication, capturing and disseminating. It encourages active and independent learning, own assessment and self- responsibility for new learning. Latest technology is progressively becoming more significant in teaching- learning process and also in the entire educational system. Objective of the problem was; to attempt for enhancing awareness about role of technology in enabling students for enhanced learning outcomes. The innovations that ICT has brought in teaching- learning process include: online student registration, online fee deposition, e- coaching, e- learning, e- communication, online results, quick access to variety of information, online published advertisement, no requirement of keeping hardcopy, easy networking human resources etc. Technology supports all kinds of teaching- learning and nothing can be achieved by neglecting the technology. Learning outcomes through self- assessment can be amplified and refined with the use of technology. It favors self- directed lifelong learning beyond the regular classroom processes. Ready availability of technological tools provides favorable circumstances for self- directed learning and enhanced learning and nothing can be achieved by neglecting the technology. Learning outcomes through self- assessment can be amplified and refined with the use of technology. It favors self- directed lifelong learning beyond the regular classroom processes. Ready availability of technological tools provides favorable circumstances for self- directed learning and enhanced learning outcomes. There are different ways in which technology supports learners to self-assess through self- directed learning, such as; e- Portfolios, video conferencing, Online Learning Resources, e- books, Open online educational resources, Social Networking, Twitter, YouTube, online publishing etc. Technology fosters a live contact between the teacher and the student through web-based learning including intranet, internet and extranet. Facilities of e- mail, online learning, CD- ROM, television, and audio- video tape are also playing an important role in teaching- learning process. Edusat technology is very powerful media for interaction of eminent persons and students. Technology has significant implications for the development and support for self-assessment by of self- directed learning. The use of multiple- choice and short- answer responses with computer- assisted assessments will continue for enhanced learning outcomes.